Receptor tyrosine kinases in Drosophila development. - Sopko, R.; Perrimon, N. (Cold Spring Harbor perspectives in biology, 2013)
Tyrosine phosphorylation plays a significant role in a wide range of cellular processes. The Drosophila genome encodes more than 20 receptor tyrosine kinases and extensive studies in the past 20 years have illustrated their diverse roles and complex signaling mechanisms. Although some receptor tyrosine kinases have highly specific functions, others strikingly are used in rather ubiquitous manners. Receptor tyrosine kinases regulate a broad expanse of processes, ranging from cell survival and proliferation to differentiation and patterning. Remarkably, different receptor tyrosine kinases share many of the same effectors and their hierarchical organization is retained in disparate biological contexts. In this comprehensive review, we summarize what is known regarding each receptor tyrosine kinase during Drosophila development. Astonishingly, very little is known for approximately half of all Drosophila receptor tyrosine kinases.